A 12-Week Randomized, Double-Blind, Placebo-Controlled Clinical Trial of Topiramate for the Treatment of Compulsive Buying Disorder. Issue 2 (March 2020) - Nicoli de Mattos, Cristiana; Kim, Hyoun S.; Marasaldi, Renata F.; Requião, Marinalva G.; de Oliveira, Elen Cristina; Zambrano Filomensky, Tatiana; Tavares, Hermano
Abstract: Background: Topiramate is an anticonvulsant that has shown promise as a pharmacological agent for the treatment of addictive disorders, including compulsive buying disorder (CBD). The aim of the present study was to examine the efficacy of topiramate in the treatment of CBD and its associated characteristics using a 12-week randomized, double-blind, placebo-controlled design. Methods: Fifty patients seeking treatment of CBD who met the inclusion criteria were randomly assigned to either the experimental group (n = 25) or the control group (n = 25). Both groups received 4 sessions of psychoeducation. Results: Forty-four participants completed the follow-up with no differences in the rate of dropout between groups. There were no differences between participants who received topiramate or placebo in reducing CBD symptoms assessed by the primary outcome scale (Yale-Brown Obsessive-Compulsive Scale – Shopping Version). However, participants who received topiramate were significantly more likely to show clinical improvement when assessed by a secondary outcome measure, the Compulsive Buying Follow-Up Scale. In addition, there was a trend among participants who received topiramate to report improvements in aspects of hoarding and impulsivity compared with the control group. There were significant improvements in comorbid depression and social adjustments over time, but no group × time interaction was found. Conclusions: The results do not provide support for the use of topiramate in the treatment of CBD. Future investigation with larger and representative samples and longer follow-up period are needed. Abstract : Supplemental digital content is available in the text.